A STUDY OF ONLINE USER’S BEHAVIOUR TOWARDS FACEBOOK SOCIAL NETWORK - ORZAN, Gheorghe; BOBOC, Andreea Larisa; BURGHELEA, Ioana; STUPU, Luana Diana (Annales Universitatis Apulensis Series Oeconomica, 2014)
The socio-economic environment provides the possibility of using the Internet in different ways in order to be accessed by the online consumers to either study, be informed, to buy, work, interact, play or even communicate. The premises of the paper are based on the research of the compartmental online utilisation focused on the time spent, the different activities in which they are engaged at that particular moment and the existing reasons behind the decisions they take within the networking, the main purpose will be however the Facebook Networking. In the paper we will address to different conceptual aspects regarding online marketing, online users behaviours, so that we can easily observe how they manifest on the Facebook platform. To predict how the online behaviour of users express within the Facebook Networking it was put together a marketing research aiming their behaviour and their future intentions of accessing the Networking.